2007
DOI: 10.1016/j.ccr.2006.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Myocardin and p16 during Malignant Transformation Contributes to a Differentiation Defect

Abstract: Myocardin is known as an important transcriptional regulator in smooth and cardiac muscle development. Here we found that myocardin is frequently repressed during human malignant transformation, contributing to a differentiation defect. We demonstrate that myocardin is a transcriptional target of TGFbeta required for TGFbeta-mediated differentiation of human fibroblasts. Serum deprivation, intact contact inhibition response, and the p16ink4a/Rb pathway contribute to myocardin induction and differentiation. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
72
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 33 publications
(39 reference statements)
11
72
0
Order By: Relevance
“…This observation is consistent with a recent report in which inactivation of myocardin is associated with malignant tumor growth (9). In addition, we demonstrate the endogenous influence of myocardin to hinder cell growth.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This observation is consistent with a recent report in which inactivation of myocardin is associated with malignant tumor growth (9). In addition, we demonstrate the endogenous influence of myocardin to hinder cell growth.…”
Section: Discussionsupporting
confidence: 82%
“…We have shown that the toggling of SRF toward growthdependent or differentiation pathways is related to interplay between myocardin and another SRF-associated factor, Elk-1, in a manner where myocardin directly competes with Elk-1 for SRF binding and antagonizes proliferative signaling induced by PDGF (7). Although previous studies have shown that overexpression of myocardin can retard cell growth (8) and inactivation of myocardin promotes tumor growth (9), the molecular mechanism related to myocardin and cellular proliferation remains unknown.…”
mentioning
confidence: 93%
“…16,25,73 TGF-b-induced responses require Smad2 and the smooth muscle transcriptional regulator myocardin. 74 The above-mentioned observations support the opinion that TGF-b is a dominant indirect proinvasive factor for epithelial cancer cells, as it converts a-SMA negative fibroblasts that do not stimulate invasion into a-SMA positive myofibroblasts that do stimulate invasion. We FIGURE 3 -Molecular cross-signaling between myofibroblasts and cancer cells.…”
Section: Characterization and Origin Of A Myofibroblastsupporting
confidence: 71%
“…Consistent with this concept, a microarray screen in human skeletal myoblasts transduced with Myocd revealed repression of many genes, including Myog (19). Moreover, Myocd inhibits cell growth (20) and malignant transformation (21), although it is unclear whether these effects are due to repression of growth-regulatory genes.…”
Section: Discussionmentioning
confidence: 55%